2019
DOI: 10.1002/edm2.90
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic steatosis in patients with acromegaly

Abstract: Objective Comorbid NAFLD is increasingly being diagnosed in patients with diabetes and nondiabetic endocrinopathies. The aim of this study was to assess hepatic steatosis noninvasively by transient elastography in patients with acromegaly. Design A cross‐sectional study including 22 patients with acromegaly. Methods Hepatic steatosis was quantified using controlled attenuation parameter (CAP) during elastography. Anthropometric measurements were obtained, serum liver function tests and lipid and hormone profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Although NAFLD is common in the community, the true prevalence of NAFLD in patients with acromegaly is unknown. In a German study in which 80% of the subjects had well-controlled acromegaly, ultrasonography (US) revealed NAFLD in 66% of the participants ( 35 ). Ciresi et al found that 61% of patients with active acromegaly at diagnosis had NAFLD determined by the US.…”
Section: Discussionmentioning
confidence: 99%
“…Although NAFLD is common in the community, the true prevalence of NAFLD in patients with acromegaly is unknown. In a German study in which 80% of the subjects had well-controlled acromegaly, ultrasonography (US) revealed NAFLD in 66% of the participants ( 35 ). Ciresi et al found that 61% of patients with active acromegaly at diagnosis had NAFLD determined by the US.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Croatia has shown lower calcaneus quantitative ultrasound parameters and increased bone turnover in male patients with active acromegaly ( 28 ). Hepatic steatosis is another comorbidity that has recently been reported at relatively high rates in patients with acromegaly, though the studies included small numbers of patients ( 29 , 30 ). Genetic markers that may help identify patients with increased risk from these comorbidities have been studied ( 30 , 31 ).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Hepatic steatosis is another comorbidity that has recently been reported at relatively high rates in patients with acromegaly, though the studies included small numbers of patients ( 29 , 30 ). Genetic markers that may help identify patients with increased risk from these comorbidities have been studied ( 30 , 31 ).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Few studies to date have shown an association between acromegaly and NAFLD prevalence, and in particular the hepatic steatosis index (HSI). Interestingly, a reduction of GH and IGF-1 levels after treatment induction in acromegaly has been associated with a reduction of the HSI ( 126 , 127 ). However, due to the relatively low prevalence of acromegaly, there is still limited data regarding its association with NAFLD and the impact of control of the disease with conventional treatments such as octreotide long-acting release on NAFLD progression or regression.…”
Section: Growth Hormone Dysregulationmentioning
confidence: 99%